2021
DOI: 10.1017/jfm.2021.1099
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic interactions and extreme particle clustering in turbulence

Abstract: Expanding recent observations by Hammond & Meng (J. Fluid Mech., vol. 921, 2021, A16), we present a range of detailed experimental data of the radial distribution function (r.d.f.) of inertial particles in isotropic turbulence for different Stokes number, $St$ , showing that the r.d.f. grows explosively with decreasing separation r, exhibiting $r^{-6}$ scaling as the collision radius is approached, regardless of $St$ or part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 37 publications
(158 reference statements)
6
54
0
Order By: Relevance
“…This might lead to interesting bifurcations similar to those seen in impacting systems [20]. We note also that Bragg et al [33] observed pairs of spheres that stuck together. These could be the result of inelastic collisions, corresponding to a third qualitatively different collision outcome.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This might lead to interesting bifurcations similar to those seen in impacting systems [20]. We note also that Bragg et al [33] observed pairs of spheres that stuck together. These could be the result of inelastic collisions, corresponding to a third qualitatively different collision outcome.…”
Section: Discussionsupporting
confidence: 66%
“…In particular it remains to be seen to which extent the spatial clustering is weakened when the flow becomes time dependent. We note that recent experimental studies [33,36] of colliding particle in turbulence show strong spatial clustering at small separations. Whether or not the clustering mechanism described above can offer an explanation of these observations, depends on whether it survives averaging over different steady linear flows, and to which extent it is weakened by stochastic driving in a time-dependent flow.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…One approach to incorporate HI is to modify our descriptions of the relative velocities and radial distributions to account for HI [e.g. 8,10]. For the purposes of this paper, we instead consider drawing values for the relative velocities and radial distributions from the relatively mature theories for noninteracting inertial particles in turbulence, and to modify the corresponding collision-rate prediction with a multiplicative collision efficiency that incorporates a physical understanding of the mechanisms by which HI reduces coalescence rates [e.g.…”
mentioning
confidence: 99%